Assessment of clinical and hematological profile in dengue fever - Patel, Mehul K.; Patel, Hitesh J. (International Journal of Advances in Medicine, 2020)
Background: Dengue is one of the most important viral diseases especially in the tropical regions. According to the WHO almost 50 million people get dengue infection annually and WHO estimates almost half of the world’s population lives in countries having endemicity for dengue infection. This study is an attempt to elucidate the positive laboratory profile of serologically diagnosed dengue patients so as to facilitate early diagnosis, treatment, management and vector control measures, to reduce the morbidity and mortality because of this disease. Methods: This study was conducted on 80 indoor patients. Patients presenting to the emergency department, outpatient department (OPD) or pediatric OPD with complaints of fever and clinical features of dengue with positive NS1 antigen test or dengue antibody serology IgM or IgG or both were included in the study. Hemogram was done on automated cell counter analyzer (Sysmex XP 100) which included hemoglobin, hematocrit, total leucocyte count (TLC), differential leucocyte count (DLC) and platelets count. Results: Raised hematocrit (>47%) was noted in 10 (16.6%) of patients at presentation and the hematocrit ranged from 20- 51%. The total leukocyte count ranged from 1500 cells/cumm to >11000 cells/cumm. Leucopenia with less than 4000 cells/cumm was present in 25 % cases. In the present study out of 80 cases of dengue fever, 85% cases had thrombocytopenia and 15% cases had severe thrombocytopenia (< 20,000/cumm) with bleeding manifestations. Conclusions: Hemoconcentration, leucopenia, thrombocytopenia, and raised liver enzymes SGOT and SGPT along with reactive/ plasmacytoid lymphocytes on peripheral smear gives enough clues to test for dengue serology so that dengue cases can be diagnosed in their initial stages.